Indeks Massa Tubuh Paling Berpengaruh Terhadap Rasio Extracellular Mass/Body Cell Mass - Myra Antonia; Maria Dara Novi Handayani; Agnes Rensa; Vetinly Vetinly (Atma Jaya Catholic University of Indonesia, 2021)
ABSTRACT Background: Extracellular mass/body cell mass (ECM/BCM) ratio is a independent predictor mortality in nutritional status and certain chronic disease. ECM/BCM ratio is influenced by various factors such as muscle mass, blood cells, bone mass, tendons, total body water, and certain chronic diseases. Objective: Determine factors associated with elderly ECM/BCM ratio in Jakarta nursing home. Methods: This observational cross-sectional study was conducted in four nursing home in Jakarta. Nutritional status measured with Mini Nutritional Assessment (MNA) score, Body Mass Index (BMI), Waist Circumference (WC), Mid-Arm Circumference (MAC), and calf circumference (CC) using measurement. ECM/BCM ratio is measured using Maltron Bioscan 916, Pearson correlation and Kendall's Tau B were used for bivariate analysis. Simple linear regression was used for multivariate analysis. Results: A total of 74 subjects were recruited (mean age 72.12 years, 71.6% women). Body mass index (p<0.05), WC (p<0.05), and CC (p<0.05) were negatively associated with ECM/BCM ratio, while MNA score (p<0.05) and age (p<0.05) were positively associated with ECM/BCM ratio. There wasn't any significant difference in TBW between male and female elderly. In the multivariate linear regression analysis, BMI was negatively associated with ECM/BCM ratio (p<0.05). Conclusions: Significant relationship were found independently between MNA score, BMI, WC,MAC, and age with ECM/BCM ratio. Body mass index is the main factor associated with ECM/BCM ratio in the elderly in Jakarta nursing homes. Our findings suggest that elderly with lower BMI have higher ECM/BCM ratio.